Copper-Catalyzed Deoxygenative C2-Sulfonylation of Quinoline N-Oxides with DABSO and Phenyldiazonium Tetrafluoroborates for the Synthesis of 2-Sulfonylquinolines via a Radical Reaction - Li, Guang-Hui; Dong, Dao-Qing; Deng, Qi; Yan, Shi-Qiang; Wang, Zu-Li (Synthesis, 2019)
An efficient and practical method for the synthesis of 2-sulfonylquinolines through copper-catalyzed deoxygenative C2-sulfonylation of quinoline N-oxides with 1,4-diazabicyclo[2.2.2]octane bis(sulfur dioxide) (DABSO) and phenyldiazonium tetrafluoroborates is demonstrated. Products with various substituents were obtained in moderate to high yields.
Keywords: quinoline N-oxides; DABSO; radicals; sulfonylation; copper